2015
DOI: 10.1155/2015/546925
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Parental Influences with Physical Activity and Screen Time among Young Children: A Systematic Review

Abstract: Parents play a critical role in developing and shaping their children's physical activity (PA) and sedentary behaviours, particularly in the early years of life. The aim of this systematic review is to identify current literature investigating associations of parental influences with both PA and screen time in young children. This systematic review was conducted in November 2013 using 6 electronic databases covering research literature from January 1998 to November 2013. Thirty articles that met inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
275
3
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(319 citation statements)
references
References 51 publications
(144 reference statements)
30
275
3
11
Order By: Relevance
“…Total screen time is recognised to predict lower levels of PA in children 43. Parents are recognised to have an important role in determining PA and sedentary behaviours of their children 44. Parents may support children to join some form of organised sports club or organisation, structured cultural activities, Youth Clubs and After-School Clubs 45.…”
Section: Discussionmentioning
confidence: 99%
“…Total screen time is recognised to predict lower levels of PA in children 43. Parents are recognised to have an important role in determining PA and sedentary behaviours of their children 44. Parents may support children to join some form of organised sports club or organisation, structured cultural activities, Youth Clubs and After-School Clubs 45.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little research in which these various factors associated with objectively measured PA have been included in the same study (Finn, Johannsen, & Specker, 2002). When it comes to parental influence through parents' own PA habits, a recent review (Xu, Wen, & Rissel, 2015) showed that parents' encouragement, support and role modelling could result in higher levels of their children's PA. Nevertheless, to the authors' knowledge, few studies have investigated objectively and simultaneously measured PA for preschool-aged children and their parents, showing positive but mainly weak associations between parental and child PA (Jago et al, 2014;Moore et al, 1991;Ruiz, Gesell, Buchowski, Lambert, & Barkin, 2011;Taylor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2016) regarded guided teaching as the combination of leading organization and discovery learning for the synergistic effect that guided teaching was therefore generated. Xu, Wen, and Rissel (2015) explained that leading organization could cover new and old knowledge and provide the optimal cognitive anchorage at proper levels to establish subordinate and supervisor relationship between subsumers in new material concepts and learners' cognition structure. In other words, a cognitive bridge was built for meaningful learning to effectively enhance students' learning outcome.…”
Section: H1mentioning
confidence: 99%